A novel technique for an alignment-insensitive density calibration of Thomson scattering diagnostics developed at W7-X. (1st March 2022) - Fuchert, G.; Nelde, P.; Pasch, E.; Beurskens, M.N.A.; Bozhenkov, S.A.; Brunner, K.J.; Meineke, J.; Scott, E.R.; Wolf, R.C.; ,
Abstract: In most laboratory setups in plasma physics, including magnetic-confinement experiments for fusion research, laser-based Thomson scattering allows for absolutely calibrated density measurements without input from other diagnostics and with high spatial resolution. A common issue is the alignment stability of either the laser beam or the observation optics. Frequent recalibrations are typically required. This is a challenge in particular for larger fusion experiments; while beam paths tend to get longer, the access for alignment and calibration gets more restricted. Therefore, simple, fast and robust calibration methods are required. A novel calibration technique has been developed at W7-X to account for alignment variations in the calibration procedure. This will decrease the pulse-to-pulse variations significantly and allow for a longer time duration before a recalibration becomes necessary. By monitoring the beam position accurately, it could be shown that misalignment leads to deterministic and reproducible changes in the measured density. The introduced density errors can be corrected for by monitoring the laser beam for every individual laser pulse. In the last experimental campaign, this has been done retrospectively by introducing parallel shifts to the laser beam path in order to show the feasibility of this method. It could be demonstrated that the impact of introduced shifts on the electron density can be successfully corrected for. For future campaigns, the beam alignment will intentionally be varied during the absolute calibration in order to cover the full range of expected beam positions. During the actual experiments, the beam positions will be monitored likewise and each density profile will be evaluated with the most suitable calibration factor. While probably not needed for W7-X, vibrations of the observation optics could be included in the same way.